Household budgetary management system for single parents and housewife / Siti Nadhirah Ahmad Tarmizi - Ahmad Tarmizi, Siti Nadhirah (2012)
Nowadays, people are unaware of the financial issues that have struck the community. Furthermore, the instability in economics and also price changes may influence the income of the society. Malaysians are also experiencing a lot of increases in food and petroleum prices nowadays. Therefore, it is important to understand how far people spend their money wisely in a situation of global economic changes. To resolve the problem, a Household Budgetary Management System was developed with the main purpose of helping the Malaysian communities' especially single parents and housewife which have difficulties in keeping track with their household budget. There are three main objectives for this research which are to identify the key elements and activities involved in budgeting, to map UCD to the design of a household budgetary management system and to develop a household budgetary management system. This project uses the User-Centered Design (UCD) methodology which the user is the main focus and actively involves in each phase throughout the whole process. By developing this system, it will help single parents and housewives to manage their financial systematically. Therefore, it can be concluded that this project assist the user in financial issues and keeping track with their household budget